1999
DOI: 10.1002/1531-8249(199906)45:6<736::aid-ana7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

ABT-431, a D1 receptor agonist prodrug, has efficacy in Parkinson's disease

Abstract: Studies in animal models show a selective D1 receptor agonist with full functional efficacy compared with dopamine to have antiparkinsonian efficacy of similar magnitude to levodopa, without the same propensity for inducing dyskinesia. To date, no such agent has been tested in humans. ABT‐431 is the prodrug of A‐86929, a full, selective D1 receptor agonist. Subjects (n = 14) with levodopa‐responsive Parkinson's disease received five doses of ABT‐431 (5, 10, 20, 30, and 40 mg) and one of placebo after a 12‐hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 20 publications
4
61
1
Order By: Relevance
“…First, D1 agonists used in the clinic have been associated with hypotension, limiting the clinical dose (Blanchet et al, 1998;Rascol et al, 1999). To date, no D1 selective compounds have been identified to delineate the role of D1 versus D5 receptors in regulating blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, D1 agonists used in the clinic have been associated with hypotension, limiting the clinical dose (Blanchet et al, 1998;Rascol et al, 1999). To date, no D1 selective compounds have been identified to delineate the role of D1 versus D5 receptors in regulating blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydrexidine showed improvement in a working memory task in patients with schizotypical personality disorder (Rosell et al, 2015). The D1 agonist prodrug ABT-431 also caused hypotension at doses that demonstrated clinical efficacy versus negative symptoms (Rascol et al, 1999). D1 and D5 receptors are expressed in vascular and renal tissues and both modulate blood pressure, although their individual roles are still being investigated (Zeng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, although D 1 receptors are traditionally considered as the pillars of dyskinesia, D 2 receptors play an important role. Thus, once priming has occurred, both D 1 and D 2 agonists can induce AIMs in the 6-OHDA-lesioned rat (Dupre et al, 2007) and dyskinesia in the MPTPlesioned NHP (Pearce et al, 1995;Fasano et al, 2010) and in idiopathic PD patients (Olanow et al, 1994;Blanchet et al, 1998a;Rascol et al, 1999Rascol et al, , 2001bSchapira et al, 2011). Moreover, viral vector-induced overexpression of RGS2-9, a guanosine triphosphatase (GTPase) protein that inhibits D 2 receptor downstream signaling, alleviated established LID in the MPTPlesioned macaque and LI-AIMs in the 6-OHDAlesioned rat (Gold et al, 2007).…”
Section: Dopamine Receptorsmentioning
confidence: 97%
“…The potential clinical utility of D 1 agonists has slowly been receiving human validation (Rascol et al, 1999;Rosell et al, 2014), although the development of an approvable drug has been inhibited by issues including pharmacokinetics, seizures, and hypotension. A functionally selective D 1 agonist could theoretically have advantages (Mailman, 2007), yet whereas some existing D 1 ligands do have some degree of functional selectivity Ryman-Rasmussen et al, 2005, no compound has yet been shown to have sufficient signaling bias to translate into meaningful pharmacological differences.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, for Parkinson's disease, the efficacy of D 1 agonists in animal models has translated into clinical trials with large effect sizes similar to those seen in the preclinical models (Rascol et al, 1999(Rascol et al, , 2001. A recent preliminary clinical study (Rosell et al, 2014) also reported significant effects on working memory consistent with predictions from preclinical models (Arnsten et al, 1994;Schneider et al, 1994;Steele et al, 1996Steele et al, , 1997.…”
mentioning
confidence: 99%